2013
DOI: 10.1186/1756-3305-6-117
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity rates for agents of canine vector-borne diseases in Spain: a multicentre study

Abstract: BackgroundControlling canine vector-borne diseases (CVBD) is a major concern, since some of these diseases are serious zoonoses. This study was designed to determine seropositivity rates in Spain for agents causing the following five CVBD: leishmaniosis (Leishmania infantum: Li), heartworm (Dirofilaria immitis: Di), ehrlichiosis (Ehrlichia canis: Ec), anaplasmosis (Anaplasma phagocytophilum/Anaplasma platys: An) and Lyme disease (Borrelia burgdorferi: Bb).MethodsAnti-An, -Bb, and -Ec antibodies and the Di anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
92
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 75 publications
19
92
2
4
Order By: Relevance
“…A possible explanation for the previous failure to detect positive cases here is that the antigen test may have given false negatives in dogs with low parasitic burdens or in blood samples from those infected only by male worms (American Heartworm Society, 2014). However, also the low-level prevalence in Iași county revealed in our study is important because, as reported by Miro et al (2013), D. immitis may serve as a reservoir of infection for other animals in low-incidence areas.…”
Section: Articlementioning
confidence: 86%
“…A possible explanation for the previous failure to detect positive cases here is that the antigen test may have given false negatives in dogs with low parasitic burdens or in blood samples from those infected only by male worms (American Heartworm Society, 2014). However, also the low-level prevalence in Iași county revealed in our study is important because, as reported by Miro et al (2013), D. immitis may serve as a reservoir of infection for other animals in low-incidence areas.…”
Section: Articlementioning
confidence: 86%
“…While in the study of Volgina et al (2013) the age of negative tested dogs was lower (2.6 years), this was not observed for the present study (n = 59; 5.8 years). In another study from Spain, even higher seropositivity for E. canis and B. burgdorferi was observed in younger dogs (< 1 year) compared to adult dogs, while no differences in the rates recorded for Anaplasma spp., D. immitis or L. infantum were identified (Miró et al 2013). Overall, different studies also failed to find any association between gender and CVBDs analysed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, different studies also failed to find any association between gender and CVBDs analysed (e.g. Villleneuve et al 2011;Miró et al 2013 Gaunt et al 2010;Dyachenko et al 2012). In fact, a potential co-infection with A. platys and E. canis is even more probable considering that they use the same tick vector (R. sanguineus), and that, based on previous studies, this latter tick appears to be a common ectoparasite of dogs in Bulgaria (Kirkova et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, Goossens et al [34] found a relatively high (17%), seroprevalence of B. burgdorferi among dogs of using whole-cell ELISA. On the other hand, lower seroprevalence rates in apparently healthy dogs were detected in Portugal (0.2%), Spain (0.4%), and Latvia (2.5%) [35][36][37]. Low seroprevalence of B. burgdorferi found among dogs in these countries could be explained by their position at the northern and southern borders of I. ricinus areal, where activity of ticks is spatially and temporally restricted, and consecutively exposure of dogs to Borreliae vectors is lower.…”
Section: Discussionmentioning
confidence: 85%